In Vitro Shoot Culture Growth of Pontianak Orange (Citrus nobilis var. microcarpa) with the Addition of Naphthalene Acetic Acid and 6-Benzyl Amino Purine - Nissa, Zoelva Zakiatun; Zakiah, Zulfa; Turnip, Masnur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Pontianak siam orange (Citrus nobilis var. microcarpa) is an important agricultural commodity unique to Sambas Regency, West Kalimantan. The demand for Pontianak siam oranges has been steadily increasing over the years, yet the production of Pontianak oranges has not been able to meet the domestic demand. The limited availability of superior seedlings is one of the reasons for this situation. Therefore, efforts are needed to fulfill the demand for Pontianak siam oranges by producing a large quantity of superior seedlings in a short period. One of the strategies that can be employed is in vitro propagation. This research aims to observe the growth of Pontianak Siamese orange shoot explants after administration of NAA (Naphthalene Acetic Acid) and BAP (6-Benzyl Amino Purine). This research was conducted from January to June 2023 at the Tissue Culture Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, Tanjungpura University. The study employed a Completely Randomized Design (CRD) with two treatment factors namely NAA concentrations with 4 levels (0; 0.25; 0.5; 0.75 mg/L), and BAP concentrations with 5 levels (0; 0.5; 1; 1.5; 2 mg/L). Parameters observed were the emergence time of shoot, shoot number, height of shoot, and the number of leaves. The results showed that single NAA, single BAP, and combination treatment of NAA and BAP significantly affected all growth parameters. Treatment with the addition of 0.25 mg/L NAA and 1 mg/L BAP (A1B2) was the treatment with the fastest shoot emergence time (2.80 days after planting), the largest number of shoots (2.60 shoots)the tallest shoots (1.50 cm), , and the greatest number of leaves (2.60 leaves).